2010
DOI: 10.1080/18811248.2010.9711948
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation Mechanisms of a Single Molten Copper Jet Penetrating a Sodium Pool—Transition from Thermal to Hydrodynamic Fragmentation in Instantaneous Contact Interface Temperatures below Its Freezing Point—

Abstract: To clarify the fragmentation mechanism of a molten metallic fuel jet in a sodium pool under highejection-velocity conditions that correspond to the medium-and high-burnup conditions in the metallic fuel core of liquid-metal-cooled fast breeder reactors, a series of experiments with molten copper as a metallic fuel simulant and a sodium pool was carried out. Under low-ejection-velocity conditions in the range of an ambient Weber number ðWe a Þ < 200, the fragmentation of the molten copper jet depends on the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…As mentioned above, the hydrodynamic interaction is considered to be an important factor in meltjet breakup. Nishimura et al (2010) suggested a hydrodynamic fragmentation model that agreed well with their copper/sodium experiments at high ambient Weber numbers (> 200). The ambient Weber…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…As mentioned above, the hydrodynamic interaction is considered to be an important factor in meltjet breakup. Nishimura et al (2010) suggested a hydrodynamic fragmentation model that agreed well with their copper/sodium experiments at high ambient Weber numbers (> 200). The ambient Weber…”
Section: Introductionsupporting
confidence: 67%
“…Fig. 12 shows the droplet MMD obtained from the present experiments and the fragment MMD obtained from the previous works: U-alloy78/water system (Matsuo et al, 2008), copper/sodium system (Nishimura et al, 2010), and aluminum-oxide/sodium system (Matsuba et al, 2016b). The vertical axes in Fig.…”
Section: Summary Of Droplet Size and Comparison With Melt-coolant Expmentioning
confidence: 82%
See 3 more Smart Citations